Investigation on semi-transparent perovskite solar cells - Yuan, Zhengtian (Nanyang Technological University, 2022)
Semi-transparent perovskite solar cell (ST-PSC) has attracted enormous attention in recent years due to its potential in building-integrating photovoltaic (BIPV), smart windows and tandem solar cells. To obtain adequate average visible transmittance (AVT) in application, an ultrathin absorber is commonly applied in ST-PSC. The thinner perovskite layer has higher transparency, but its light absorption ability reduces and the device shows low current density and poor efficiency. This work investigates a number of strategies to achieve high efficiency ST-PSC. Two different electron transport materials (BaSnO3 and SnO2) were developed to fabricate semi-transparent solar cells. These two electron transport layers show high transparency and great conductivity in photovoltaic application. Besides that, a high quality ITO transparent electrode was obtained, and a thin silver film was used as buffer layer to protect the hole transport layer (HTL) and sensitive perovskite film. More importantly, a new 2D material MXene was utilized for surface passivation to improve the semi-transparent perovskite device performances. The terminal fluorine and OH- groups absorbed onto MXene improve the perovskite crystallization process and led to larger perovskite grains and less grain boundaries, which is favorable for carrier transport. The interfacial carrier recombination decreased due to the fewer defects in perovskite layer, and consequently the current density of the devices with MXene increased significantly. The semi-transparent perovskite devices based on BSO electron transport layer (ETL) and SnO2/MXene achieved power conversion efficiency (PCE) of 9.14% with 18% AVT and PCE of 14.78% with AVT over 22%, respectively. This work provides a new strategy to prepare high efficiency ST-PSCs with remarkable average visible transmittance.